2017
DOI: 10.1016/j.neuron.2017.09.005
|View full text |Cite|
|
Sign up to set email alerts
|

Consolidation Promotes the Emergence of Representational Overlap in the Hippocampus and Medial Prefrontal Cortex

Abstract: Summary Structured knowledge is thought to form, in part, through the extraction and representation of regularities across overlapping experiences. However, little is known about how consolidation processes may transform novel episodic memories to reflect such regularities. In a multi-day fMRI study, participants encoded trial-unique associations that shared features with other trials. Multi-variate pattern analyses were used to measure neural similarity across overlapping and non-overlapping memories during i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
163
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 210 publications
(184 citation statements)
references
References 99 publications
(143 reference statements)
16
163
5
Order By: Relevance
“…These data align with a large body of research focusing on how context or task representations are learned, stored, and used in future tasks. What has emerged from this research is that mPFC represents overlapping prior experiences (Tompary et al, ), or “schemas”, which can also provide scaffolding for integrating and learning new information (Gilboa & Marlatte, ; Preston & Eichenbaum, ; Tse et al, , ; van Kesteren, Rijpkema, Ruiter, Morris, & Fernández, ).…”
Section: Proactive Mechanisms Of Binding Sequential Memory Representamentioning
confidence: 99%
See 1 more Smart Citation
“…These data align with a large body of research focusing on how context or task representations are learned, stored, and used in future tasks. What has emerged from this research is that mPFC represents overlapping prior experiences (Tompary et al, ), or “schemas”, which can also provide scaffolding for integrating and learning new information (Gilboa & Marlatte, ; Preston & Eichenbaum, ; Tse et al, , ; van Kesteren, Rijpkema, Ruiter, Morris, & Fernández, ).…”
Section: Proactive Mechanisms Of Binding Sequential Memory Representamentioning
confidence: 99%
“…(b) Results showed that participants were more likely to remember items from the same context as appearing closer together in the sequence; in contrast, participants were more likely to remember items that had spanned a context shift as having appeared farther apart in the sequence. (c) Ratings of closer temporal proximity were associated with greater hippocampal pattern similarity across event boundaries (adapted from "Similarity breeds proximity: Pattern similarity within and across contexts is related to later mnemonic judgments of temporal proximity" by Ezzyat and Davachi, 2014, Neuron, 81(5), p. 1179-1189 [Color figure can be viewed at wileyonlinelibrary.com] (Tompary et al, 2017), or "schemas", which can also provide scaffolding for integrating and learning new information (Gilboa & Marlatte, 2017;Preston & Eichenbaum, 2013;Tse et al, 2007Tse et al, , 2011van Kesteren, Rijpkema, Ruiter, Morris, & Fernández, 2014).…”
Section: Proactive Mechanisms Of Binding Sequential Memory Represenmentioning
confidence: 99%
“…How two memories become integrated, however, is still open to debate. Some theories propose that integration occurs during the encoding of the second memory (i.e., integrative encoding; Nadel, Hupbach, Gomez, & Newman‐Smith, ; Sekeres, Winocur, & Moscovitch, ), while others propose that integration occurs during consolidation or retrieval (i.e., offline integration; Polyn, Norman, & Kahana, ; Tompary & Davachi, ). These processes are not mutually exclusive however, meaning memory integration could theoretically occur both during encoding and during offline periods (Zeithamova & Preston, ).…”
Section: Episodic Memories Are Integrated Across Event Boundariesmentioning
confidence: 99%
“…Any knowledge of link between A and C would suggest that the distinct memory traces AB and BC have become integrated. Evidence suggests humans are remarkably adept at such inferential tasks (e.g., Backus, Schoffelen, Szebényi, Hanslmayr, & Doeller, 2016;Schlichting, Zeithamova, & Preston, 2014;Tompary & Davachi, 2017;Zeithamova, Dominick, & Preston, 2012). How two memories become integrated, however, is still open to debate.…”
Section: Episodic Memories Are Integrated Across Event Boundariesmentioning
confidence: 99%
“…In a 2017 study with Alexa Tompary, then a graduate student in her lab, Davachi showed volunteers pictures of 128 objects, each paired with one of four scenes -a beach scene appeared with a mug, for example, and then a keyboard; a cityscape was paired with an umbrella, and so on. Each object appeared with only one scene, but many different objects appeared with the same scene 11 . At first, when the volunteers matched the objects to their corresponding scenes, each object elicited a different brain-activation pattern.…”
Section: Melding Memoriesmentioning
confidence: 99%